2006
DOI: 10.1155/imrn/2006/95181
|View full text |Cite
|
Sign up to set email alerts
|

Szego limit theorem for operators with discontinuous symbols and applications to entanglement entropy

Abstract: Abstract. The main result in this paper is a one term Szegö type asymptotic formula with a sharp remainder estimate for a class of integral operators of the pseudodifferential type with symbols which are allowed to be non-smooth or discontinuous in both position and momentum. The simplest example of such symbol is the product of the characteristic functions of two compact sets, one in real space and the other in momentum space. The results of this paper are used in a study of the violation of the area entropy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Gioev [19] has recently confirmed that the second term in the asymptotics of tr f (T r ) is of the order predicted by…”
Section: Second Order Asymptotics Of the Eigenvalue Distribution Formentioning
confidence: 73%
“…Gioev [19] has recently confirmed that the second term in the asymptotics of tr f (T r ) is of the order predicted by…”
Section: Second Order Asymptotics Of the Eigenvalue Distribution Formentioning
confidence: 73%
“…Once this theorem is proved, the asymptotics can be closed with the help of the sharp bounds (12.11) and (12.17), which were derived in [11], [12] using the abstract version of the Szegő formula with a remainder estimate obtained in [21] (see also [22]).…”
Section: Resultsmentioning
confidence: 99%
“…Before discussing behaviour of the variance of the number of particles in a disordered metal, we remind the reader its behaviour in the absence of disorder. As is well known, for k F L 1 the particle-number variance becomes [4,19,20]:…”
Section: Formalismmentioning
confidence: 89%